ANALISIS RASIO KEUANGAN SEBAGAI ALAT UKUR KINERJA PERUSAHAAN PADA PT. ASTALIA MILLENIA EDUCATINDO CABANG MADIUN - Satrijo Budi Wibowo (Assets: Jurnal Akuntansi dan Pendidikan, 2013)
This study aims to determine the company's financial performance , both in terms of liquidity, solvency, profitability and activity of PT .Millennia Astalia Educatindo Madiun from 2010 until 2012. The processed data is the data that comprises the financial statements of the balance sheet and income statement. Methods of data processing by using ratio analysis consisting of the ratio liquidity, profitability, solvency and activities. The method used is descriptive method, the research seeks to collect and present data from the company to be analyzed so as to provide a fairly clear picture of the object under study. Because of financial ratios is one tool in evaluating the company's financial condition and performance , it is expected that through the analysis of financial statements may consideration in making decisions, especially regarding the financial condition in the future. Besides, the analysis of financial statements to describe the company's actual financial performance. The results showed that the ratio of liquidity include the current ratio and quick ratio increased, although still below the industry average. For profitability ratios include gross profit margin and operating profit margin increased in 2012 despite the decline was due to the increased cost of goods sold. Solvency ratios while covering a total debt to equity ratio and total debt to capital assets shows a marked improvement by decreasing solvency ratio from year to year. Nonetheless Solvency ratio still can’t to be categorized either as it is still above the industry average. The ratio of activity which includes receivable turnover and total asset turnover has fluctuated, rising in 2011 but dropped in 2012. Nonetheless Activity ratios are well below the industry average, which means the company has not been effective in utilizing existing resources.